Percutaneous coronary angioplasty versus coronary artery bypass grafting in treatment of unprotected left main stenosis (NOBLE): a prospective, randomised, open-label, non-inferiority trial. - Mäkikallio, T; Holm, NR; Lindsay, M; Spence, MS; Erglis, A; Menown, IB; Trovik, T; Eskola, M; Romppanen, H; Kellerth, T; Ravkilde, J; Jensen, LO; et al. (Elsevier, 2016)
Background Coronary artery bypass grafting (CABG) is the standard treatment for revascularization in patients with left main coronary artery (LMCA) disease, but use of percutaneous coronary intervention (PCI) for this indication is increasing. We compared PCI and CABG for treatment of LMCA disease. Methods Patients with LMCA disease were enrolled in 36 centers and randomized 1:1 to treatment with PCI or CABG. Eligible patients had stable angina pectoris, unstable angina pectoris or non-ST elevation myocardial infarction. The primary endpoint was major adverse cardiac or cerebrovascular events (MACCE) - a composite of all-cause mortality, non-procedural myocardial infarction, any repeat coronary revascularization and stroke. The primary outcome was test for non-inferiority of PCI to CABG after up to 5 years of follow-up. Results A total of 1201 patients were randomized. Kaplan-Meier five-year estimates of MACCE were 28.7% for PCI and 20.1% for CABG, HR 1.46 [95% confidence interval (CI), 1.10 to 1.95], exceeding the limit for non-inferiority and significant for superiority of CABG over PCI (p=0.0078). Comparing PCI to CABG, five-year estimates were 11.5% vs. 9.5% [HR 1.04 (95% CI, 0.65 to 1.67), p=0.86] for all-cause mortality; 6.9% vs. 1.9% [HR 2.9 (95% CI, 1.40 to 5.90), p=0.004] for non-procedural myocardial infarction; 16.2% vs. 10.4% [HR 1.5 (95% CI, 1.04 to 2.17), p=0.03] for any revascularization; and 4.9% vs 1.7% [HR 2.3 (95% CI, 0.92 to 5.48), p=0.07] for stroke. Conclusion CABG provided a clinical outcome superior to PCI for treatment of LMCA disease.